PENGARUH SUHU TERHADAP PRODUKSI ASAM LEVULINAT DARI INULIN UMBI DAHLIA (Dahlia Sp.) - Murwindra, Rosa; Sikumbang, Saryono; Awaliddin, Amir; Linggawati, Amilia (Sistem Informasi, 2016)
Dahlia is a floriculture plant with tuber that rich in inulin. Inulin is soluble in hot water and it will settle on cool temperature in alcohol. The inulin extraction to use hot water from dahlia tuber take from Bukittinggi of West Sumatra. Extraction result from 100 g dahlia tuber is 4% inulin (w/w dahlia tuber), such as inulin flour is white gray. As qualitative test with Seliwanoff and Nelson-Somogyi methods, that inulin positive contain of fructose and reducing sugar. This inulin can be converted into levulinic acid using acid catalyst at high temperature. Production of levulinic acid with variate reaction temperature from 130 â 170 oC. The reaction of inulin convertion is done in ampul that burned in oven. In this experiment, conversion of inulin to be levulinic acid is high 26,25% (w/w inulin) using acid catalyst of hydrochloride acid 1 M and heating 170 oC about 15 minutes.